PENGARUH KUALITAS PELAYANA DAN CITRA KOPERASI TERHADAP PARTISIPASI ANGGOTA KOPERASI PLASMA SAWT BUKIT SANDIANG TIGO BAWAN KAB. AGAM - Jean Elikal Marna; Yunia Wardi (Program Magister Pendidikan Ekonomi (S2), 2014)
The purpose of this research is to analyze the effect of service quality and image of the cooperative to cooperative member participation in koperasi Plasma Sawit Bukit Sandiang Tigo Bawan Kab.Agam. The hypotheses were (1) the effect of service quality to the cooperative image,(2) the effect of service quality and cooperative image to the participation of cooperative members. This research was descriptive associative. The population in this study was a cooperative member of the Koperasi Plasma Bukit Sandiang Tigo Bawan Kab.Agam, totaling 73 people with the sampling technique was Proportional random sampling. The technique of data analysis was descriptive analysis, classical assumption test: test for normality and homogeneity, path analysis, and hypothesis testing using the F test and t test. The results showed that: 1) There was a significant influence on the quality of service to the cooperative's images, 2) There was a significant effect of service quality and cooperative image on the cooperative participation of cooperative members. Based on the above results it can be concluded that in order to increase the participation of cooperative members in Koperasi Plasma Sawit Bukit Sandiang Tigo Kab.Agam suggested to further improve service quality and image of the cooperative